APPLICATION OF OCCUPATIONAL SAFETY AND HEALTH TRANS METRO ON BUS DRIVERS PEKANBARU CITY - makomulamin amin; Dwi Musliha Putri (Jurnal Kesehatan Komunitas, 2020)
In 2013 are 2 cases an accident that results in 1 person died.So also in 2014 by one case of an accident resulted in 1 person died and some case of an accident else has happened. This showed that the high the number of accident caused by bus trans metro the city of pekanbaru. The purpose of this study is to find the application of work safety and health on the bus driver trans metro the city of pekanbaru. The kind of research used to research this is observational with the quantitative approach analytic with the design research cross sectional. A population of subjects as many as 100 composed of entire the bus driver trans metro pekanbaru with the sample of the 80 people. Technique the sample used is by means random simple. Test results bivariate show that the training pvalue = 0,001, work experiences pvalue = 0,001, the health condition of pvalue = 0,688, Stress pvalue = 0,834 work, and SOP pvalue = 0,002. From test bivariate it can be concluded that a significant relation exists between training, work experiences and SOP by the application of health and safety work at a bus driver trans metro city pekanbaru. Expected to transportation department city pekanbaru communication information, improve the quality of the driver work by granting provision education and training in an effort to prevent an accident in stages and sustainable appropriate tasks and responsibilities